MAP Yemen - International Food Policy Research Institute; Ministry of Planning and International Cooperation; Development Seed (International Food Policy Research Institute, 2019)
MAP Yemen is a monitoring tool that keeps track of agriculture, nutrition, and rural development projects in Yemen and their socio-economic context. The ultimate goal of the tool is to improve development project planning, coordination and effectiveness. Specifically, MAP Yemen helps the Government, development partners, researchers and other interested parties to gain a quick overview of the state of food and nutrition security in Yemen at the aggregate and the project level. The tool has been developed for and with the Ministry of Planning and International Cooperation (MOPIC) by the International Food Policy Research Institute (IFPRI) in collaboration with Development Seed and as part of a Gesellschaft für Internationale Zusammenarbeit (GIZ) funded-project. In order to effectively allocate funds, build synergies and evaluate future proposals, users can visualize and monitor the status and progress of agricultural projects categorized by sector, location, donor or common objectives, as well as track key performance indicators related to the project. In order to contextualize projects and evaluate which governorates /districts require further assistance, users can also quickly map, zoom in and chart a wide-range of indicators on food and nutrition security, poverty and development across Yemen, with a focus on monitoring progress towards the Sustainable Development Goals (SDGs) - on the national and subnational level.